Conviviality as a Tool for Creating Networks The Case of an Early Modern Global Peasant Traveller - Gil Montero, Raquel (2019)
In this paper, we analyse an unusual travel account from the seventeenth century. Besides the rarity of travel accounts from this period, its singularity resides primarily in the fact that the traveller, Gregorio de Robles, self-identified as a peasant. This exceptional Spaniard travelled dominions of the Spanish, Portuguese, British, French, and Dutch empires in America and Europe, and even briefly touched Southern Africa. His travel account is rich in information, but here we focus on one specific aspect: conviviality with the people he encountered along his way, with a special emphasis on his fellow compatriots. We will argue that this conviviality allowed Robles to create new networks and accumulate social capital and that the relationship with his paisanos resignified his belonging. By moving and traveling, he could attain a more privileged position than he had apparently been enjoying in his Castilian hometown.